THE INFLUENCE OF YOUTUBE ON STUDENT CREATIVITY IN ART CULTURE AND WORKS (SBdP) LESSONS IN THE COVID-19 PANDEMIC - Sisriawan Lapasere; Herlina Herlina; Dedi Rore Poting (Jurnal Dikdas, 2021)
This study aims to determine the effect of the use of YouTube social media on student creativity in the fourth grade subjects of cultural arts and crafts (SBdP) at SDN Nunu. This research is a quantitative study using an experimental approach using two groups, namely the experimental class group and the control class group. The design used in this research is the design "Noneqiuvalent Control Group Design". The subjects in this study were some of the fourth grade students of SDN Nunu with a total of 30 students consisting of two classes, namely class IVA as the experimental group and class IVB as the control group. The instrument used was a figural creativity test. The data analysis technique used was the normality test and the homogeneity test as a prerequisite for the t-test. Based on the results of testing the hypothesis that the experimental and control groups have a T-count of 5.280 with a T-table of 2.042, so that the significant (2-tailed) value of the posttest T-Test results of the two groups is 0.000, so the null hypothesis H0 is rejected and the Ha hypothesis is accepted because based on the T-Test test criteria the significance value is <0.05. Thus it can be concluded that there is an influence of the influence of the use of YouTube social media on student creativity in the fourth grade subjects of cultural arts and crafts (SBdP) at SDN Nunu.